Tailoring the selectivity of ultralow-power heterojunction gas sensors by noble metal nanoparticle functionalization. (October 2021) - Lupan, Oleg; Ababii, Nicolai; Santos-Carballal, David; Terasa, Maik-Ivo; Magariu, Nicolae; Zappa, Dario; Comini, Elisabetta; Pauporté, Thierry; Siebert, Leonard; Faupel, Franz; Vahl, Alexander; Hansen, Sandra; et al.
Abstract: Heterojunctions are used in solar cells and optoelectronics applications owing to their excellent electrical and structural properties. Recently, these energy-efficient systems have also been employed as sensors to distinguish between individual gases within mixtures. Through a simple and versatile functionalization approach using noble metal nanoparticles, the sensing properties of heterojunctions can be controlled at the nanoscopic scale. This work reports the nanoparticle surface functionalization of TiO2 /CuO/Cu2 O mixed oxide heterostructures, where the gas sensing selectivity of the material is tuned to achieve versatile sensors with ultra-low power consumption. Functionalization with Ag or AgPt-nanoclusters (5–15 nm diameter), changed the selectivity from ethanol to butanol vapour, whereas Pd-nanocluster functionalization shifts the selectivity from the alcohols to hydrogen. The fabricated sensors show excellent low power consumption below 1 nW. To gain insight into the selectivity mechanism, density functional theory (DFT) calculations have been carried out to simulate the adsorption of H2, C2 H5 OH and n -C4 H9 OH at the noble metal nanoparticle decorated ternary heterostructure interface. These calculations also show a decrease in the work function by 2.6 eV with respect to the pristine ternary heterojunctions. This work lays the foundation for the production of a highly versatile array of sensors of ultra-low power consumption with applications for the detection of individual gases in a mixture. Graphical Abstract: ga1 Highlights: Noble NP functionalization and thickness control tune selectivity and sensitivity. Ultra-low energy consumption of up to 1 nW with large gas responses of 390%. Highly sensitive detection of H2 and VOCs vapours at low concentrations of a few ppm. Deposition of metal nanodots reduces the work function of ternary heterojunctions. DFT calculations elucidate the sensing mechanism of the functionalized junctions.